2012
DOI: 10.1007/s10865-012-9474-5
|View full text |Cite
|
Sign up to set email alerts
|

Parental support, internalizing symptoms, perceived health status, and quality of life in adolescents with congenital heart disease: influences and reciprocal effects

Abstract: Caring for adolescents with congenital heart disease requires attention to physical health but also to psychosocial functioning. Identifying how such psychosocial variables influence one another over time is important for designing health care strategies. The present study examined how depressive symptoms, loneliness, paternal and maternal support, and quality of life predicted one another. A total of 429 mid- to late adolescents with congenital heart disease (53.4 % boys) participated in a three-wave longitud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 32 publications
4
60
0
2
Order By: Relevance
“…Third, most studies focused on maternal support, excluding paternal support. However, recent research has demonstrated that paternal support predicted psychological functioning of adolescents with CHD 9 months later (Luyckx et al, 2012a). Consequently, the present studies focused on both maternal and paternal support, in addition to peer support.…”
Section: Introductionmentioning
confidence: 94%
See 2 more Smart Citations
“…Third, most studies focused on maternal support, excluding paternal support. However, recent research has demonstrated that paternal support predicted psychological functioning of adolescents with CHD 9 months later (Luyckx et al, 2012a). Consequently, the present studies focused on both maternal and paternal support, in addition to peer support.…”
Section: Introductionmentioning
confidence: 94%
“…The combined presence of maternal and paternal support was found to be important (Luyckx et al, 2012a). Paternal support might become especially important for adolescents with a chronic condition, as fathers tend to encourage independence more than mothers do (Shulman & Seiffge-Krenke, 1997).…”
Section: Social Support Clusters and Comparison With Healthy Peersmentioning
confidence: 99%
See 1 more Smart Citation
“…Health-related functioning problems (e.g., pain) were related to negative changes in QOL, while benefit finding (e.g., potential benefits of illness) and character strengths (e.g., vitality) were associated with positive changes. Researchers in Belgium examined factors linked with changes over time in global perceived QOL for 429 adolescents with congenital heart disease aged 14–18 years, using a linear analogue scale from 0 (‘worst life’) to 100 (‘best life’) [26, 27]. Over an 18-month follow-up, findings showed both depressive symptoms and loneliness were negatively related, and paternal support positively related, to QOL changes [27].…”
Section: Introductionmentioning
confidence: 99%
“…As to the associations between parental social support and child-reported HRQoL, some studies [16,34] reported positive correlations. In contrast, we found no associations.…”
Section: Discussionmentioning
confidence: 99%